Involvement of the liver-gut peripheral neural axis in nonalcoholic fatty liver disease pathologies via hepatic HTR2A - Takashi Owaki; Kenya Kamimura; Masayoshi Ko; Itsuo Nagayama; Takuro Nagoya; Osamu Shibata; Chiyumi Oda; Shinichi Morita; Atsushi Kimura; Takeki Sato; Toru Setsu; Akira Sakamaki; et al. (The Company of Biologists, 2022)
Serotonin (5-HT) is one of the key bioamines of nonalcoholic fatty liver disease (NAFLD). Its mechanism of action in autonomic neural signal pathways remains unexplained; hence, we evaluated the involvement of 5-HT and related signaling pathways via autonomic nerves in NAFLD. Diet-induced NAFLD animal models were developed using wild-type and melanocortin 4 receptor (MC4R) knockout (MC4RKO) mice, and the effects of the autonomic neural axis on NAFLD physiology, 5-HT and its receptors (HTRs), and lipid metabolism-related genes were assessed by applying hepatic nerve blockade. Hepatic neural blockade retarded the progression of NAFLD by reducing 5-HT in the small intestine, hepatic HTR2A and hepatic lipogenic gene expression, and treatment with an HTR2A antagonist reproduced these effects. The effects were milder in MC4RKO mice, and brain 5-HT and HTR2C expression did not correlate with peripheral neural blockade. Our study demonstrates that the autonomic liver-gut neural axis is involved in the etiology of diet-induced NAFLD and that 5-HT and HTR2A are key factors, implying that the modulation of the axis and use of HTR2A antagonists are potentially novel therapeutic strategies for NAFLD treatment. This article has an associated First Person interview with the first author of the paper.